(untitled) - Martin, Bill; 1916-2004.; Ehlert, Lois (New York, 2011)
Illustrations and rhyming text follow ten caterpillars as one wriggles up a flower stem, another sails across a garden pool, and one reaches an apple leaf, where something amazing happens.
Keywords: Caterpillars; Fiction; Stories in rhyme